THE BOD-COD REDUCTION IN LEACHATE WATER USING RICE HUSK ASH - Shohifah Annur; Tiur Elysabeth; Ahmad fajri; Rudi Apandi (Jurusan Kimia FMIPA Universitas Lampung, 2022)
The purpose of this research is investigating the effect of rice husk ash in reducing of BOD, COD and TSS in leachate water. In this research, the protype of water purifier was created and the rice husk was conducted in this instrument. Before using as an adsorbent, the rice husk ash was heated at furnace at 500 °C. The process of water purifying using rice husk as an adsorbent was performed from 0 min to 120 min. The BOD-COD levels and the TSS content in leachate water was investigated before and after purifying using rice husk ash. The BOD level at this time was decreased from 412.5 to 126.25mg/L during contact time optimum 45 min.. The optimum time in reducing COD was also reduced from 861.0 to 261.25 mg/L during 45 min respectively. After 45 min , the content of BOD and COD was increased. The TSS content of leachate water after treatment using rice husk ash was changed from 99.0 to 5.0 mg/L after 30 min contact with rice husk. We conclude that the rice husk was effective in decreasing BOD, COD and TSS in leachate water.Keywords: Rice husk ash, BOD, COD.